2000
DOI: 10.1016/s0020-7225(99)00048-8
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of macroscopic filtration law for transient linear viscoelastic fluid flow in porous media

Abstract: This work is concerned with deriving a macroscopic ®ltration law for describing transient linear viscoelastic ¯uid ¯ow in porous media. This is performed using a homogenisation technique, i.e. by upscaling the heterogeneity scale description. The macroscopic ®ltration law is expressed in Fourier space as a generalised Darcy's law with a dynamic permeability tensor. This model is valid at low Reynolds and Deborah numbers. Analytical results are determined in the particular case of the ¯ow of an Oldroyd ¯uid in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 10 publications
0
40
0
2
Order By: Relevance
“…See [37] for an efficient numerical method and [23] for an analytic study of the filtration laws, corresponding to the power and Carreau law viscosities. (b) For the (formal) homogenization of a linear Oldroyd fluid in a bundle of capillary tubes at low Reynolds and Deborah numbers see [43] . Very little is known concerning filtration laws for non-Newtonian fluids, which are more complicated than the quasi-Newtonian ones discussed in this chapter.…”
Section: Concluding Remarks On Filtration Laws For Non-newtonian Fluidsmentioning
confidence: 99%
“…See [37] for an efficient numerical method and [23] for an analytic study of the filtration laws, corresponding to the power and Carreau law viscosities. (b) For the (formal) homogenization of a linear Oldroyd fluid in a bundle of capillary tubes at low Reynolds and Deborah numbers see [43] . Very little is known concerning filtration laws for non-Newtonian fluids, which are more complicated than the quasi-Newtonian ones discussed in this chapter.…”
Section: Concluding Remarks On Filtration Laws For Non-newtonian Fluidsmentioning
confidence: 99%
“…Under the assumption of low Reynolds number based on the pore dimension, the generalized Darcy's law (7) is also derived by [20] using a homogenization theory.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Therefore, the neutral temporal stability curve is obtained for ω i = 0, which selects dominant modes at the onset of convection. Substituting Equations (20), (21) into (12)- (15), linearizing the equations and applying the curl twice to the momentum balance equation, one can obtain:…”
Section: Infinite Aspect Ratiosmentioning
confidence: 99%
“…Koshiba et al [120] investigated the viscoelastic flow through an undulating channel as a model for flow paths in porous media and concluded that the stress in the flow through the undulating channel should rapidly increase with increasing flow rate because of the stretch-thickening elongational viscosity. Khuzhayorov et al [121] applied a homogenization technique to derive a macroscopic filtration law for describing transient linear viscoelastic fluid flow in porous media. The results obtained in the particular case of the flow of an Oldroyd fluid in a bundle of capillary tubes show that viscoelastic behavior strongly differs from Newtonian behavior.…”
Section: Dilatancy At High Flow Ratesmentioning
confidence: 99%